Developing and validating a scale for measuring pre-service Chinese as an additional language teacher beliefs - Li, Chili; Yi, Ting; Zhang, Shuang; Ma, Chunyan; Liu, Honggang (Frontiers in Psychology, 2022)
Teacher beliefs are a pivotal psychological quality for sustainable teacher development. Previous studies have mainly focused on the beliefs of English-as-a-second/foreign-language (ESL/EFL) teachers, while little attention has been paid to those of Chinese-as-an-additional-language (CAL) teachers. Particularly, there is a paucity of effort made to develop and validate instrument for measuring pre-service CAL teacher beliefs. Therefore, to further quantify the beliefs of CAL teachers is increasingly called for as an essential means to help teachers sensitize their beliefs system and promote teacher development as a sustainable goal. To be specific, the present study aims to construct a scale for gauging beliefs of pre-service CAL teachers. It firstly conceptualizes the dimensions of pre-service CAL teacher beliefs by means of semantic analysis with ROST CM6, and then cross-validates the reliability and validity of the scale with psychometric methods. Two independent samples composed of 221 and 222 pre-service CAL teachers participated in a questionnaire survey. The two samples were utilized for later Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) respectively. The two data sets have satisfactory psychometric results, all confirming that the scale subsumes three factors: Beliefs about Chinese Language Teaching, Beliefs about Chinese Language, and Beliefs about Chinese Language Learners. The scale validated in the present study contributes to research on pre-service CAL teacher beliefs, and provides implications for sustainable pre-service CAL teacher training.